Genetic analysis of polyketide synthase and peptide synthase genes of ‎cyanobacteria as a mining tool for new pharmaceutical compounds - Bahareh Nowruzi; Hossein Fahimi; Neda Ordodari; Reza Assareh (Islamic Azad University, 2017)
Cyanobacteria are considered a promising source for new ‎pharmaceutical lead compounds and a large number of chemically diverse and ‎bioactive metabolites have been obtained from cyanobacteria. Despite of ‎several worldwide studies on prevalence of NRPSs and PKSs among the ‎cyanobacteria, none of them included Iranian cyanobacteria of Kermanshah ‎province. Therefore, the aim of this study was to amplify the NRPS and PKS ‎genes. These stains were the most frequent species of that zone. The DNA ‎sequences of the 16s rRNA region were determined and the strains were named ‎as Scytonema sp. N11, Calothrix sp. N42 and terrestrial Nostoc SP. N66). ‎Lastly, to show that the presence of these genes correlates with natural product ‎synthesis, we conducted biochemical assays to detect the presence of ‎antimicrobial effects in organic extracts. The results of these experiments ‎suggest that both NRPS and PKS genes are presence in all three strains. ‎Finally the sequences presented in this study have been deposited in GenBank ‎for getting the accession numbers (NRPS A domains) and (PKS KS domains). ‎According to these results, it is concluded that the antibiogram bioassay and ‎molecular detection of peptide synthetase and polyketide synthase genes in ‎cyanobacterial strains may be useful techniques for the assessment of natural ‎product -producing species and possible role of peptide synthetase and ‎polyketide synthase enzyme complexes in the biosynthesis of biologically ‎active compounds.‎